2020
DOI: 10.15761/vdt.1000177
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the progression of immunoglobulin-G4-related abdominal aortic aneurysms after endovascular therapy

Abstract: Objective: Approximately half of inflammatory abdominal aortic aneurysms, defined by the prominent thickening adventitia, are immunoglobulin G4 (IgG4)related diseases characterized by elevated serum IgG4 and IgG4-positive-plasmacytes infiltration. IgG4-related AAAs (IgG4-AAAs) exhibit vasculitis with elevated inflammatory marker levels. Matrix metalloproteinases (MMPs) degrade the extracellular matrix to destroy the aortic structures to progress aneurysm. This report examined pre-and postoperative serum MMPs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Regarding EVT of IgG4-related aneurysms, we have reported 14 cases of endovascular aneurysmal repair for abdominal aortic aneurysms. 22 However, in that study, we found that EVT did not improve lesions related to IgG4-RD. 22 Thus, open surgical repair has been recommended.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Regarding EVT of IgG4-related aneurysms, we have reported 14 cases of endovascular aneurysmal repair for abdominal aortic aneurysms. 22 However, in that study, we found that EVT did not improve lesions related to IgG4-RD. 22 Thus, open surgical repair has been recommended.…”
Section: Discussionmentioning
confidence: 61%
“… 22 However, in that study, we found that EVT did not improve lesions related to IgG4-RD. 22 Thus, open surgical repair has been recommended. 22 Furthermore, the number of reported cases of IgG4-related medium-size arterial aneurysms has been extremely small.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation